Evaluation of Factors Causing a Delay in Management and Hospital Stay in Diabetic Foot Amputation Patients: A Prospective Cohort Study - Tahir, Syeda Anjala; Bhatti, Shaheen; Huma, Zille; Khan, Muhammad Ahsan; Rehman, Areeba; Tahir, Shumaila; Abbasi, Amanullah (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: To determine the rate of different amputation levels in diabetic foot patients and the incidence of repetitive foot surgeries and evaluate the factors causing a delay in hospital stay and amputation of patients. METHODOLOGY: This prospective cohort study was conducted in Dr. Ruth K.M. Pfau, Civil Hospital Karachi, Pakistan. The study selected 375 participants from the clinic’s daily patient inflow from October 2021 to March 2022 using a non-probability consecutive sampling technique. Those who had a delay in hospital stay and amputation were further followed up from May - October 2022. The chi-square test and Kruskal Wallis test (p-value <0.05) were used to correlate the effect of the level of lower limb amputation and the cause of delay in amputation using SPSS version 24.0. RESULTS: Total 246(65.60%) were males and 129(34.40%) were females. Toe amputation was the most commonly seen amputation in 173(46.1%) participants. About 168(44.8%) patients had some in-hospital delay stay during their treatment. Preoperative hurdles (Uncontrolled RBS, Osteomyelitis, etc.) were the most common factor causing an in-hospital delay in 92(24.5%) patients. The level of amputation performed was found to be statistically significant with factors causing a delay in hospital stay through chi-square (p=0.003*) and Kruskal Wallis test H (2) statistic= 13.3, df = 3, H (2), P=0.004*). CONCLUSION: Diabetic foot is a frequent cause of amputation globally, majorly in developing countries like Pakistan. On-time provision of treatment to these patients can decline the global amputation rate due to diabetic foot ulcers.